Quantum plateau of Andreev reflection induced by spin-orbit coupling. (8th January 2015) - Xu, Luting; Li, Xin-Qi
Abstract: In this work we uncover an interesting quantum plateau behavior for the Andreev reflection between a one-dimensional quantum wire and superconductor. The quantum plateau is achieved by properly tuning the interplay of the spin-orbit coupling within the quantum wire and its tunnel coupling to the superconductor. This plateau behavior is justified to be unique by excluding possible existences in the cases associated with multi-channel quantum wire, the Blonder-Tinkham-Klapwijk continuous model with a barrier, and lattice system with on-site impurity at the interface.